Subcutaneous Enoxaparin for Systemic Anticoagulation of COVID-19 Patients During Extracorporeal Life Support - Marion Wiegele; Daniel Laxar; Eva Schaden; Eva Schaden; Andreas Baierl; Mathias Maleczek; Mathias Maleczek; Paul Knöbl; Martina Hermann; Martina Hermann; Alexander Hermann; Christian Zauner; et al. (Frontiers in Medicine, 2022)
BackgroundExtracorporeal membrane oxygenation, with an inherent requirement for anticoagulation to avoid circuit thrombosis, is a key element in the treatment of respiratory failure associated with COVID-19. Anticoagulation remains challenging, the standard of care being intravenous continuous administration of unfractionated heparin. Yet regimens vary. Some intensive care units in our center have successfully used enoxaparin subcutaneously in recent years and throughout the pandemic.MethodsWe retrospectively analyzed adult COVID-19 patients with respiratory failure who had been systemically anticoagulated using either enoxaparin or unfractionated heparin. The choice of anticoagulant therapy was based on the standard of the intensive care unit. Defined thromboembolic and hemorrhagic events were analyzed as study endpoints.ResultsOf 98 patients, 62 had received enoxaparin and 36 unfractionated heparin. All hazard ratios for the thromboembolic (3.43; 95% CI: 1.08–10.87; p = 0.04), hemorrhagic (2.58; 95% CI: 1.03–6.48; p = 0.04), and composite (2.86; 95% CI: 1.41–5.92; p = 0.007) endpoints favored enoxaparin, whose efficient administration was verified by peak levels of anti-factor Xa (median: 0.45 IU ml−1; IQR: 0.38; 0.56). Activated partial thromboplastin time as well as thrombin time differed significantly (both p<0.001) between groups mirroring the effect of unfractionated heparin.ConclusionsThis study demonstrates the successful use of subcutaneous enoxaparin for systemic anticoagulation in patients with COVID-19 during extracorporeal membrane oxygenation. Our findings are to be confirmed by future prospective, randomized, controlled trials.